Dementia-friendly communities: The involvement of people living with dementia. (May 2022) - Mathie, Elspeth; Antony, Arthur; Killett, Anne; Darlington, Nicole; Buckner, Stefanie; Lafortune, Louise; Mayrhofer, Andrea; Dickinson, Angela; Woodward, Michael; Goodman, Claire
Background: Dementia Friendly Communities (DFCs) offer an approach to community engagement to improve the lives of people living with dementia and their family supporters. The involvement of those living with dementia is key to creating successful DFCs. This paper examines how people affected by dementia were involved in developing and designing DFCs in England, and the impact of their involvement. Methods: This study used a mixed method case study design in six DFCs in England. Data collection involved documentary analysis, a survey, and interviews and focus groups with service providers and people living with dementia and their supporters. Findings: All six DFCs aspired to involve people living with dementia and their family supporters, but often relied on a small number of people living with dementia. The range of involvement activities in DFCs included Steering Group meetings, wider public consultations, and enabling feedback through data collection methods such as surveys and 'ad hoc' conversations. Organisations within the DFCs with experience of public consultation offered structured opportunities for involvement. There was no evidence of people living with dementia initiating or co-leading the organisation, its direction and/or the activities of the DFCs. Conclusion: The involvement of people living with dementia in DFCs went beyond rhetoric, with some evidence of context sensitive and meaningful participation. Approaches towards involvement should focus on involvement in strategic planning, and on harnessing expertise in delivering different involvement activities to optimise participation of a greater breadth of people living with dementia. Engagement with local organisations who work with, and for, people living with dementia, and dedicating the resources needed for involvement work, are crucial for creating DFCs. The success of DFCs are determined by how the needs of people living with dementia are identified, discussed and reviewed by those within the community who are most affected.